Increased Bacterial Richness Associated With Lesions Within the Porites spp. of Vietnam - Rasmussen, Linett; Barnes, Christopher; Mak, Sarah Siu Tze; Kjartansdóttir, Kristín Rós; Hansen, Thomas Arn; Doan-Nhu, Hai; Nguyen-Ngoc, Lam; Guldberg Frøslev, Tobias; Hellström, Micaela; Hansen, Anders Johannes (Frontiers in Ecology and Evolution, 2020)
Coral reefs worldwide are rapidly declining due to increasing anthropogenic stressors and environmental changes, with large-scale mortalities of coral reefs observed in many locations across the globe. It has become clear that the microbiome of corals is important in understanding the causes of coral infections, although its exact role is yet to be fully understood. Here, we characterize the bacteria and fungi associated with the non-lesional and lesional (identified by discoloration and tissue loss) tissues of coral species from Vietnam. Metabarcoding of the bacterial 16S rRNA gene and the fungal ITS rRNA gene region were performed. We sampled across two Porites species with potentially multiple causes of stresses, yet the bacterial compositions of lesional regions were consistently different from non-lesional areas of the same coral. These differences were driven by a considerable and significant increase in OTU richness within the lesional region compared to the non-lesional region. While no single OTU was consistently associated with lesional tissue, indicator analysis revealed that nine OTUs were significantly more persistent in the lesional regions that could represent useful bioindicators of stress. Meanwhile, there were no indicator OTUs in the non-lesional region. Further investigations are needed to determine whether changing bacterial communities play a mechanistic role in inducing lesioning, or are opportunistically colonizing stressed corals.